Jeszcze o wieloparadygmatyczności i dylematach lingwistyki na progu trzeciego tysiąclecia = A Few More Reflections on Multiparadigmatism and the Dilemmas of Linguistics at the Onset of the Third Millennium - Jędrzejko, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article opens with a summary characteristics of the present-day stage of the evolution of Polish linguistics (which, not infrequently, parallels the state of affairs in theoretical language studies of other countries), concentrating primarily upon the dominant traits of linguistics "after structuralism", i.e.: the shift towards research encompassing the whole space of the forms of "parole", the blurring of the distinction between synchrony and diachrony, between the various planes of the language, the simultaneity of multifaceted approaches to language and language studies, the interdisciplinarity of language studies, the reopened connection between research on language and broadly understood culture, culture studies, as well as cross-disciplinary insights into a variety of cognitive mechanisms, etc.
Keywords: strukturalizm; poststrukturalizm; kognitywizm; komunikacjonizm; etnolingwistyka; tekstologia; pragmatyka komunikacji; structuralism; poststructuralism; cognitivism; communicationism; ethnolinguistics; textology; the pragmatics of communication